Cultural identity of Malay Bugis: a reflection in traditional food practices - Naim Misran, Norsyahidatun; Md. Sharif, Mohd. Shazali; Akbarruddin, Mohd Noor Azmin; Saad, Mazni; Muhammed Yusoff, Abdullah (UiTM Press, 2022)
Buginese or Bugis traditional food is one of the most valuable cultural heritages to ensure the continuity of traditional food among the younger generations to avoid it vanishing over time. The practise of traditional food brings nostalgia and evokes one's memories that are close to their heart. It symbolised one's identity and culture, which cannot be replaced with anything today. The traditional food practises are always associated with the cultural occasions held in the community since the usage of ingredients is commonly based on their availability in the surrounding area. However, the main problem observed among the Malay Bugis was that these practises faded due to the size of the population and technologies.Based on the interviews conducted, Bugis' traditional food practises among the youths are thematically analysed by examining their level of understanding of Bugis' traditional food and the factors that contributed to their practise pattern. It shows that the neglect of Bugis' traditional food practises has slowly taken place among the youths, but it does not encompass all aspects of the practice. The study results successfully explain the phenomenon and the researchers are hopeful that they can contribute to the development of traditional food literature, particularly in other sub-ethnic groups in Malaysia.